2013
DOI: 10.5897/ajps11.306
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of aluminum toxicity on OM4900 rice seedlings by sodium silicate

Abstract: Silicon has versatile functions in plant biology, especially in plant defense and tolerance to both biotic and abiotic stressors. In this study, it was investigated if silicon could reduce the toxic effect of aluminum on rice. Aluminum was applied to OM4900 rice seedlings, and then their growth and sugar metabolism were determined. At doses of aluminum chloride of 100 and 200 µM, plant height was significantly enhanced and root elongation was reduced. The accumulation of photosynthetic pigments was tightly cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
1
7
0
2
Order By: Relevance
“…Likewise, our experiments also demonstrated that chlorophyll concentrations increased in young leaves of Al-treated Cotaxtla, Huimanguillo and Temporalero plants (Figures 3A–C , respectively). These results are also in full agreement with those reported by Nhan and Hai ( 2013 ) in rice plant cultivar OM4900, since both chlorophyll a and b were significantly higher in plants treated with 200, 300, 400, and 500 μM AlCl 3 , as compared with the control.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Likewise, our experiments also demonstrated that chlorophyll concentrations increased in young leaves of Al-treated Cotaxtla, Huimanguillo and Temporalero plants (Figures 3A–C , respectively). These results are also in full agreement with those reported by Nhan and Hai ( 2013 ) in rice plant cultivar OM4900, since both chlorophyll a and b were significantly higher in plants treated with 200, 300, 400, and 500 μM AlCl 3 , as compared with the control.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, tea plants ( Camellia sinensis ) exposed to 100 μM Al developed better than those grown in Al-free media (Hajiboland et al, 2013a ). In rice cultivar OM4900, Nhan and Hai ( 2013 ) found an increase of 35% in shoot height in plants exposed to 400 μM Al for 8 days. Moreover, Famoso et al ( 2011 ) reported that exposure to 160 μM Al triggered significant root elongation in rice, which is similar to our results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In rice, the first report indicated that Al stimulates growth [27]; later, in an analysis by the genome-wide association (GWA) on 383 different rice accessions in response to Al, 16 cultivars were reported to show an increase in root growth [12]. Subsequently, Al was reported to have increased the concentration of chlorophylls ( a and b ) and carotenoids [28]. Recently, it was observed that 200 μM Al in 4 cultivars (Cotaxtla, Tres Ríos, Huimanguillo, and Temporalero) stimulated growth, increased the concentrations of chlorophylls and total soluble sugars in the plantlet, and augmented P and K concentrations in the root [1].…”
Section: Introductionmentioning
confidence: 99%
“…Silicon applications can be effective at alleviating toxicity of metals including Al, Mn, Fe, Cd, Pb, and Zn ( Gu et al, 2012; Maksimović et al, 2012; Bharwana et al, 2013; Dufey et al, 2013; Nhan and Hai , 2013). The responsible mechanisms are complex and can be divided into external ( e.g.…”
Section: Silicon Uptake and Use By Cropsmentioning
confidence: 99%